Imagining school autonomy in high-performing education systems: East Asia as a source of policy referencing in England. Issue 6 (1st November 2016) - You, Yun; Morris, Paul
Abstract : Education reform is increasingly based on emulating the features of 'world-class' systems that top international attainment surveys and, in England specifically, East Asia is referenced as the 'inspiration' for their education reforms. However, the extent to which the features identified by the UK Government accord with the situation within East Asia is problematic. This paper examines the relationship between the English representation and the 'reality' of East Asian education systems, using school autonomy as an illustrative example. We focus on Singapore, Hong Kong and Shanghai, which are cited extensively to legitimate policies providing greater autonomy for schools in England. We argue firstly that the English representation has been largely discursive and inaccurate; has failed to recognise the variations across the region; and has been selected to endorse the Government's ideological preferences. Secondly, the scope, form and nature of school autonomy vary markedly, and are operationalised in each society in ways reflecting the prevailing sociopolitical priorities.